COMPARISONS OF SOME GRAMMATICAL AND LEXICAL CHARACTERISTICS OF THE MACEDONIAN LANGUAGE AND OTHER WORLD LANGUAGES THROUGH THE PRISM OF THE SAPIR-WHORF HYPOTHESIS - Sveto Toevski (Philological Studies, 2019)
The Sapir - Whorf hypothesis has been re-actualized in recent years and proves that languages with their grammatical, lexical and other structure significantly affect the thought - cognitive abilities of the speakers of the respective languages. Through the prism of Sapir Worth's hypothesis, respectively, from the aspect of linguistic relativity and linguistic determinism, in this paper we analyze comparatively some important grammatical and lexical characteristics of the standard Macedonian language and eight other world languages - Hopi, Chinese, Amondava, English, Nuuchahnulth, Shona, Eskimo and Japanese. We focus on the linguistic conceptualization and expression of physical time, also on the predication and in the indigenous languages, which have no real sentence with regular internal syntactic relations as in the developed languages. The goal of our analysis is also what kind of word orders are functioning and how in languages and what effects are producing polysemy and platisemy in the lexical systems of languages.